Protective mechanism of Wnt4 gene on Parkinson's disease (PD) transgenic Drosophila. - Wu, W.; Han, Y.; Fan, X.; Li, Q.; Sun, L. (International Journal of Neuroscience, 2019)
The main pathological change of Parkinson's disease (PD) is progressive degeneration and necrosis of dopaminergic neurons in the midbrain, forming a Lewy body in many of the remaining neurons. Studies have found that in transgenic Drosophila, mutations in the PTEN-inducible kinase 1 (PINK1) gene may cause indirect flight muscle defects in Drosophila, and mitochondrial structural dysfunction as well. In this study, Wnt4 gene overexpression and knockdown were performed in PINK1 mutant PD transgenic Drosophila, and the protective effect of Wnt4 gene on PD transgenic Drosophila and its possible mechanism were explored. The Wnt4 gene was screened in the previous experiment; And by using the PD transgenic Drosophila model of the MHC-Gal4/UAS system, the PINK1 gene could be specifically activated in the Drosophila muscle tissue. In PINK1 mutation transgenic fruit flies, the Wnt4 gene to study its implication on PD transgenic fruit flies' wing normality and flight ability. We found that overexpression of Wnt4 gene significantly reduced abnormality rate of PD transgenic Drosophila and improved its flight ability, and then, increased ATP concentration, enhanced mitochondrial membrane potential and normalized mitochondrial morphology were found. All of these findings suggested Wnt4 gene may have a protective effect on PD transgenic fruit flies. Furthermore, in Wnt4 gene overexpression PD transgenic Drosophila, down-regulation autophagy and apoptosis-related proteins Ref(2)P, Pro-Caspase3, and up-regulation of Beclin1, Atg8a, Bcl2 protein were confirmed by Western Blotting. The results imply that the restoring of mitochondrial function though Wnt4 gene overexpression in the PINK1 mutant transgenic Drosophila may be related to autophagy and/or apoptosis.